An Investigative Analysis of English Learning Strategy of a Successful Bilingual Learner - Nurwahida Nurwahida; Hardiani Ardin (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2021)
This study investigated the issue of learning strategy applied by a student in Bilingual program in Mathematics and Science Faculty, the State University of Makassar. It would focus on the strategy that is applied by the successful student in bilingual program. In fact, the existence of bilingual program actually has raised some worries for some people. The successful of bilingual program has been debatable because this was the first bilingual program in the State University of Makassar, which was established and run in Mathematics and Science Faculty. Many people have wondered about the successful of bilingual program in delivering teaching process by two languages instruction, in which the content as well as the language form are presented mostly in English. Therefore, the researcher was intrigued to focus her study on the successful learner who was able to show good performance in English as well as the subject matter, which is mathematics. This study scrutinized strategies applied by the successful student in learning English by using deep interview and questionnaires. There were two questionnaires used in this research namely inventory of language learning strategies by good language learner (GLL) by Rubin and inventory of language learning strategies (SILL) by Oxford. These instruments helped the researcher to investigate which strategies mostly applied by the student. In addition, the interview was employed to explore other factors that might have affected or supported the student’s learning. The finding shows that the successful learner at bilingual program of FMIPA UNM tends to use a variety of learning strategies in their learning. Although it cannot be said that one strategy is better than the other strategies, yet, it is true that the varied strategies the students use, the better performance they could gain.